Fast Response to Small Signals with Noise in Neurons - Svirskis, G. (Nonlinear Analysis: Modelling and Control, 2003)
Neurons in the brain receive synaptic inputs delivered as random trains. Mathematical theory was developed to relate the rate of threshold crossings with statistics of membrane fluctuations evoked by random point input process. Integrate-and-fire neuronal model was used to check validity of theoretical results. Mathematical theory approximated firing rate for low level of activity and showed that dependence of threshold crossings on mean rate of membrane potential change brings about very fast response to small signals.
Keywords: neuron; stochastic process; firing rate